2015
DOI: 10.4238/2015.june.11.10
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between PPARD rs2016520 polymorphism and coronary heart disease in a Han Chinese population

Abstract: ABSTRACT. PPARD encodes peroxisome proliferator-activated receptor delta, which has been shown to play an important role in controlling lipid metabolism and atherosclerosis. In this case-control study, we explored the relationship between PPARD rs2016520 polymorphism and coronary heart disease (CHD) in a Han Chinese population. A total of 657 CHD cases and 640 controls were included in the association study. rs2016520 polymorphism genotyping was performed using the melting temperature-shift polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…In contrast, association between the SNP and higher HDL values has been reported in Scottish and Canadian studies [27,28]. No relation was found with SBP in this study, while others have related the minor allele with lower blood pressure in Chinese population [32,68].…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast, association between the SNP and higher HDL values has been reported in Scottish and Canadian studies [27,28]. No relation was found with SBP in this study, while others have related the minor allele with lower blood pressure in Chinese population [32,68].…”
Section: Discussioncontrasting
confidence: 97%
“…In mice, expression of PPARδ is related to prognosis and metastatic ability of breast cancer cells 38 . Polymorphisms of PPARD and PPARG are associated with risk and prognosis of many diseases, including cardiovascular disease, diabetes, brain diseases, medulloblastoma and other cancers [39][40][41] . In our study, we firstly observed that PPARD polymorphisms (rs2016520, rs67056409 and rs1053049) were significantly associated with glioma risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several SNPs in PPARD, including rs2016520 and rs9794, were found to be associated with CVDs [1,7]. In addition, the PPARD SNP rs2016520 (+294C) seemed to be significantly associated with cholesterol metabolism and the risk of CAD [11,26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that LncPPARD regulates the expression of neighboring protein-coding genes. PPARD, with its direct target genes ADRP and ANGPTL4 , might serve as a novel biomarker for CAD, particularly when combined with risk factors [9,10], since the positive association between PPARD polymorphism rs2016520 and CAD had previously been reported [11]. In this study, three novel polymorphic variants located in the intron of PPARD, namely, rs3777744, rs3798343, and rs6922548, were selected to further investigate the genetic mechanisms by which PPARD impacts the prevalence of CAD.…”
Section: Introductionmentioning
confidence: 99%